Nasal leiomyoma presenting as sphenopalatine neuralgia: a case report and literature review - E-ting, Wannitta Wong; Saniasiaya, Jeyasakthy; Abdul Ghani, Fauzah; Ibrahim, Azliza; Tze, Liang Loh; Zakaria, Atiqah Farah (University of Toronto * Medical Society, 2023)
Leiomyoma of the nasal cavity constitutes less than 1 of all leiomyoma cases and is known to occur predominantly among the adult female population. Traditionally, intranasal leiomyoma presents with nasal obstruction and epistaxis. Herein, we report a case of solid-pattern leiomyoma arising from the right inferior turbinate, presenting exclusively as severe right jaw and neck pain, made worse by neck movements, swallowing, and even sneezing. Pain was associated with facial spasm and had significant impact on her quality of life. Endoscopic excision of the tumour successfully alleviated the patient’s symptoms, requiring no further management. An extensive literature search revealed that intranasal leiomyoma could be successfully managed by endoscopic excision with no recurrence. We highlight the importance of a thorough intranasal endoscopic examination in all patients with persistent neuropathic pain of the head and neck.